2008
DOI: 10.1149/1.2801372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Modeling of the Cell Resistance in Anode-Supported Solid Oxide Fuel Cells

Abstract: The impedance of anode-supported single cells [ Ni∕8 yttria-stabilized zirconia (YSZ) anode; La0.58Sr0.4Co0.2Fe0.8normalO3−δ cathode; 8YSZ electrolyte; area 1cm2 ] was characterized in a broad measuring range of temperature and air/fuel gas composition. The data has been analyzed by calculating the distribution function of relaxation times (DRTs). DRT computations enabled us to separate five different loss mechanisms occurring inside the cathode and anode without the need of an equivalent circuit. Two proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
509
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(564 citation statements)
references
References 15 publications
28
509
1
9
Order By: Relevance
“…arc at 0.5 Hz, as shown in Fig. 6d, is associated with slower adsorption/desorption of oxygen on the electrode surface, 16,17 which is in agreement with an order of magnitude higher surface exchange coefficient for PNO (e.g. 2 × 10 −6 cm s −1 vs. 4 × 10 −7 cm s −1 in NNO at 750…”
Section: Resultssupporting
confidence: 77%
“…arc at 0.5 Hz, as shown in Fig. 6d, is associated with slower adsorption/desorption of oxygen on the electrode surface, 16,17 which is in agreement with an order of magnitude higher surface exchange coefficient for PNO (e.g. 2 × 10 −6 cm s −1 vs. 4 × 10 −7 cm s −1 in NNO at 750…”
Section: Resultssupporting
confidence: 77%
“…In order to obtain information about the electrochemical processes and their parameter dependencies, type B cells were tested under variation of the partial pressure of steam at the anode (pH 2 O an ) and the partial pressure of oxygen at the cathode (pO 2,cat ). The distribution of relaxation times (DRT) method [15] and the subsequent CNLS-fitting of a physically motivated equivalent circuit [17] were applied to obtain an accurate electrochemical analysis of the measured cells. The low-frequency arcs of the spectra show a significant sensitivity to the variation of pH 2 O an , whereas the highfrequency arcs exhibit a low sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the polarization processes related to the charge transfer reaction at the anode exhibit an increasing resistance for increasing pH 2 O an . The anodic activation polarization processes P 2A and P 3A are formed by the complex coupling of ionic transport, gas transport and the electrochemical fuel oxidation [17]. For cermet anodes, it has been shown that these processes decrease with increasing pH 2 O an .…”
Section: Figure 21: Arrhenius Plot Of the Cathode Activation Polarizamentioning
confidence: 99%
“…In this study, the distribution of relaxation time (DRT) related to the electrochemical processes were directly calculated from the experimental impedance spectra as similar to the previous papers. 30,31 Polarization impedance Z pol (½) are considered to be an equivalent circuit composed of an infinite number of RC elements in the following series:…”
Section: Electrochemical and Catalytic Evaluationmentioning
confidence: 99%